2020
DOI: 10.1101/2020.04.02.20050997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute liver injury and its association with death risk of patients with COVID-19: a hospital-based prospective case-cohort study

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a newly respiratory infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) with multiple organ injuries. The aim of this study was to analyze SARS-CoV-2-induced acute liver injury (ALI), its association with death risk and prognosis after discharge.Methods: Three-hundred and fifty-five COVID-19 patients were recruited. Clinical data were collected from electronic medical records. ALI was evaluated and its prognosis was tracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…In addition to impaired respiratory function, function of other organs could also be damaged. Complications including cardiac injury, acute kidney injury, acute gastrointestinal injury, coagulopathy, and liver dysfunction are relatively common in critically ill cases 4,5 and were confirmed associated with poor outcome in COVID‐19 patients 6‐10 . These organs damage is considered resulting from the cytokine release syndrome (CRS) which plays pivotal role in the progression of COVID‐19 patients 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to impaired respiratory function, function of other organs could also be damaged. Complications including cardiac injury, acute kidney injury, acute gastrointestinal injury, coagulopathy, and liver dysfunction are relatively common in critically ill cases 4,5 and were confirmed associated with poor outcome in COVID‐19 patients 6‐10 . These organs damage is considered resulting from the cytokine release syndrome (CRS) which plays pivotal role in the progression of COVID‐19 patients 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have demonstrated that COVID-19 patients were accompanied with multiple organ injuries, mainly including acute liver injury, acute kidney injury, respiratory failure and even lymphopenia [12][13][14][15]. In the present study, myocardial injury was evaluated through measuring biochemical indexes, such as CK, CKMB, LDH and AST.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies found that SARS-CoV-2 mainly evoked severe acute respiratory syndrome. More and more researches revealed that most cases were prone to suffer multiple organ injuries, such as immune system disorder, acute kidney injure and even liver dysfunction [11][12][13]. Nevertheless, the clinical characteristics of myocardial injury caused by SARS-CoV-2 are rarely described.…”
Section: Introductionmentioning
confidence: 99%
“…Around half of the eligible studies (n=29, 46.8%) showed an association between the severity of COVID-19 and the degree of liver injury. [11][12][13][14][15][16][17][19][20][21][22][23]28,29,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Out of the 27 studies assessing liver injury in COVID-19, 44.4% (n=12) had pre-defined clinical criteria for liver injury, whereas 55.6% (n=15) did not have any specific pre-defined criteria. The details of these studies are given below.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…They have mentioned liver enzyme elevation without commenting on the clinical signs of hepatic dysfunction, which include hepatomegaly, ascites, and jaundice. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]32 The incidence of liver injury has varied widely across studies, from 4.8% to a striking 78%. However, the term 'liver injury' has not been defined uniformly.…”
Section: Incidence Of Liver Injury In Patients With Covid-19mentioning
confidence: 99%